Splitting and lasing of whispering gallery modes in quantum dot micropillars. - Jones,BD; Oxborrow,M; Astratov,VN; Hopkinson,M; Tahraoui,A; Skolnick,MS; Fox,AM (Optics Express, 2010)
We have studied the whispering gallery mode (WGM) resonances of GaAs/AlGaAs microcavity pillars containing InAs quantum dots. High quality factor WGMs are observed from a wide range of pillars with diameters from 1.2 to 50 μm. Multimode lasing with sub-milliwatt thresholds and high beta-factors approaching unity is observed under optical pumping in a 4 μm diameter pillar. Mode splitting is observed in WGMs from pillars with diameters of 5 μm, 20 μm and 50 μm.We develop a model in which the mode splitting in the larger pillars is caused by resonant scattering from the quantum dots themselves. The model explains why splittings are observed in all of the larger pillars and that the splitting decreases with increasing wavelength. Numerical simulations by COMSOL confirm that the model is plausible. This mechanism of splitting should be general for all circular resonant structures containing quantum dots such as microdisks, rings, toroids, and microspheres.